2020
DOI: 10.3389/fgene.2020.00999
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs Are Regulators of Diverse Animal Transcriptomes: One Health Perspective

Abstract: Derived from linear (parental) precursor mRNA, circRNA are recycled exons and introns whose ends are ligated. By titrating microRNAs and RNA binding proteins, circRNA interconnect networks of competing endogenous RNAs. Without altering chromosomal DNA, circRNA regulates skeletal muscle development and proliferation, lactation, ovulation, brain development, and responses to infections and metabolic stress. This review integrates emerging knowledge of circRNA activity coming from genome-wide characterizations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…The identification of circular RNAs in highly divergent species raises interesting questions about their evolutionary history, and functions ( Wang et al, 2014 ; Ji et al, 2019 ; Zucko and Boris-Lawrie, 2020 ). Li et al (2019) , who reviewed this topic, reported wide discrepancies: some studies claimed that circRNAs are evolutionarily highly conserved molecules, while others believe they are species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of circular RNAs in highly divergent species raises interesting questions about their evolutionary history, and functions ( Wang et al, 2014 ; Ji et al, 2019 ; Zucko and Boris-Lawrie, 2020 ). Li et al (2019) , who reviewed this topic, reported wide discrepancies: some studies claimed that circRNAs are evolutionarily highly conserved molecules, while others believe they are species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, circRNAs overall transcript levels in brain steadily grow during the developmental and aging phases, from embryonic to adulthood (28,29). Circular RNAs expression during four different developmental stages (2,6,21, and 104 weeks) in rat brain tissues was previously studied, showing an increase in abundance as rats aged (30).…”
Section: Circrnas In Normal Condition Of the Nerve System Expression And Distributionmentioning
confidence: 99%
“…However, instead of combating diseases, farmers can select animals based on the genetic resistance of health traits, which has been regarded as a sustainable method [ 14 , 15 ]. Together with genetic markers, targeting epigenetic markers and miRNAs have been regarded as a further strategy for combating livestock diseases [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%